Response of microbiota to exogenous inoculation improved the enzymatic activities of medium-temperature Daqu - Pan, Qianglin; Huang, Jun; Zhang, Suyi; Qin, Hui; Wang, Xiaojun; Mu, Yu; Tang, Huifang; Zhou, Rongqing (Frontiers in Microbiology, 2022)
To Explore the potential mechanism of improving enzymatic activities in medium-temperature Daqu (MTD) by inoculation functional isolates, we inoculated a single strain of Bacillus licheniformis, and the microbiota composed of Bacillus velezensis and Bacillus subtilis in MTD to investigate the association between the response of the functional microbiota and the enzymatic activity. The results showed that the bacterial community of MTD might be more sensitive to bioturbation than the fungal community, and the indigenous microbiota responded to the single strain more than to the microbiota. Moreover, the differential microorganisms mainly included Lactobacillales, Bacillales, and Saccharomycetales between the conventional and fortified samples. Notably, the composition of functional microbiota related to liquefying activity (LA) and saccharifying activity (SA) were significantly different, changing from Lactobacillus and Rhizomucor to Bacillus, Weissella, and Hyphopichia. That might be closely related to the effect of the bioturbation on LA (31.33%) and SA (43.54%) associated microorganisms was more tellingly. Furthermore, the relative abundance changes of bioturbation-sensitive modules in the co-occurrence network might also lead to the difference in enzymatic activities. Therefore, the LA and SA of MTD were improved by bioturbation significantly. These results provide diverse insights into the exogenous functional isolates to regulate the MTD microbiota and improve enzymatic activities.